2017
DOI: 10.1177/0260106017727359
|View full text |Cite
|
Sign up to set email alerts
|

Combined exercise training reduces climacteric symptoms without the additive effects of isoflavone supplementation: A clinical, controlled, randomised, double-blind study

Abstract: A period of 10 weeks of combined training was effective in improving climacteric symptoms in post-menopausal women. However, isoflavone supplementation did not promote additional effects in improving symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 24 publications
0
9
1
1
Order By: Relevance
“…Several trial studies also showed that isoflavone supplementation alleviated insomnia or sleep disorders among climacteric women [ 28 , 29 , 30 , 31 ]. However, other trial studies of isoflavone supplementation in climacteric women or androgen-deprived males found no significant improvement in insomnia or sleep quality [ 32 , 33 , 34 ]. Meanwhile, another randomized, placebo-controlled, double-blinded trial over six months performed on climacteric women indicated that insomnia was more frequent in the isoflavone supplementation group [ 35 ], and the longitudinal study reported that soy milk (one of the main food sources for isoflavone intake in the study) was positively related to falling asleep in the daytime among males [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several trial studies also showed that isoflavone supplementation alleviated insomnia or sleep disorders among climacteric women [ 28 , 29 , 30 , 31 ]. However, other trial studies of isoflavone supplementation in climacteric women or androgen-deprived males found no significant improvement in insomnia or sleep quality [ 32 , 33 , 34 ]. Meanwhile, another randomized, placebo-controlled, double-blinded trial over six months performed on climacteric women indicated that insomnia was more frequent in the isoflavone supplementation group [ 35 ], and the longitudinal study reported that soy milk (one of the main food sources for isoflavone intake in the study) was positively related to falling asleep in the daytime among males [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus far, several trial studies have explored the relationship between total isoflavone supplementation and sleep in climacteric women or androgen-deprived prostate cancer patients, with mixed findings, including improvement of sleep problems [ 28 , 29 , 30 , 31 ], no significant association [ 32 , 33 , 34 ], and even insomnia aggravation [ 35 ]. Only two observational studies have evaluated the association of total isoflavone consumption with sleep status among general adults and results showed that total isoflavone consumption was positively related to sleep quality and optimal sleep duration in Japanese adults and inversely associated with long sleep duration in Chinese adults [ 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…As a possible limitation, we report that there is no group without exercise as an intervention, no control of antihypertensive drug classes and doses, and the small sample size that could lead to type 2 error. Finally, we reiterate the importance of physical exercises after menopause regardless of the existence of hypertension, since, besides autonomic control alterations, they can generate improvements in blood pressure 23,32,33 , lipid profile 15 , endothelial function 34 , oxidative profile 35 , climacteric simptoms 36 , and general cardiovascular health 33,37 .…”
Section: Discussionmentioning
confidence: 90%
“…As far as menopause-specific QOL is concerned, both aerobic and resistance training, whether alone or together with nutritional supplements or educational initiatives, have been shown to improve climacteric symptoms in postmenopausal women [47,48]. In addition, such exercises alone may positively affect the impact of menopausal symptoms on QOL, as well as on psychological health and depression [49].…”
Section: Discussionmentioning
confidence: 99%